Children born during the hunger season are at a higher risk of severe acute malnutrition: Findings from a Guinea Sahelian ecological zone in Northern Ghana - Engelbert A. Nonterah (Maternal and Child Nutrition, 2022)
Abstract Heightened food insecurity in the hunger season increases the risk of severe acute malnutrition (SAM) in childhood. This study examined the association of season of birth with SAM in a Guinean Sahelian ecological zone. We analyzed routine health and sociodemographic surveillance data from the Navrongo Health and Socio‐demographic Surveillance System collected between 2011 and 2018. January–June, the period of highest food insecurity, was defined as the hunger season. We defined moderate acute malnutrition as child mid‐upper arm circumference (MUAC) between 115 mm and 135 mm and SAM as MAUC ≤ 115 mm. We used adjusted logistic regression to quantify the association between the season of birth and SAM in children aged 6–35 months. From the 29,452 children studied, 24% had moderate acute malnutrition. Overall, 1.4% had SAM, with a higher prevalence (1.8%) in the hunger season of birth. Compared with those born October–December, adjusted odds ratios (aOR) and 95% confidence interval (95% CI) for SAM were increased for children born in the hunger season: January–March (1.77 [1.31–2.39]) and April–June (1.92 [1.44–2.56]). Low birth weight, age at an assessment of nutritional status, and ethno‐linguistic group were also significantly associated with SAM in adjusted analyses. Our study established that being born in the hunger season is associated with a higher risk of severe acute malnutrition. The result implies improvement in the food supply to pregnant and lactating mothers through sustainable agriculture or food system change targeting the hunger season may reduce the burden of severe acute malnutrition.